Organizational development from the perspective of learning - Solf Zárate, Arturo (2003)
Organizational Development is analyzed from a learning. Related perspective, in congruence with the major existing literary contributions, and goes on to discuss characteristics inherent to a learning organization- as well as identifying possible courses of action that may be deemed conducive to the development of an organization of such type. Finally, a series of comments are elaborated with regard to the shortcomings to this approach.